Analysis of technique and tactics of world famous table tennis players with pen-hold grip - Hao, Y.; Hao, Z.; Zhen, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In the history of the development of table tennis, most of the players from China and other Asian countries adopted the pen-hold grip. In contrast almost all of the European players adopted the handshake grip (Fengde, 2003). In the past 20 years, due to the lack of new creativity in the pen-hold grip, a number of Asian players have changed to the hand-shake grip (Xia,. et al, 2006). However, in recent years, the pen-hold grip has made some new innovations and achieved excellent results. This paper aims to analyse and research the characteristics of the technique and tactics of the pen-hold grip of the top 3 players in the world, Lin Ma, Hao Wang, Ryu Seungmin. Study findings will supply scientific theory and reference data for inheriting and developing Asia`s traditional way of playing table tennis.